Engaging young African American women breast cancer survivors: A novel storytelling approach to identify patient‐centred research priorities. (9th January 2020) - Yan, Alice; Millon-Underwood, Sandra; Walker, Alonzo; Patten, Caitlin; Nevels, Debra; Dookeran, Keith; Hennessy, Rose; Knobloch, Mary Jo; Egede, Leonard; Stolley, Melinda
Abstract: Background: Patient‐centredness is considered an essential aspiration of a high‐quality health‐care system, and patient engagement is a critical precursor to patient‐centred care. Objectives: To engage patients, health‐care providers and stakeholders in identifying recommendations to address research and practice gaps that impact young African American breast cancer survivors. Methods: This paper reported an approach for research priority setting. This approach applies an engagement process (January‐September 2018) of using patient and stakeholder groups, patient storytelling workshops and a culminating storytelling conference in Wisconsin to generate relevant research topics and recommendations. Topics were prioritized using an iterative engagement process. Research priorities and recommendation were ranked over the conference by counting participants' anonymous votes. Results: One hundred attendees (43 patients/family members, 20 providers/researchers and 37 community members) participated in the conference. Five topics were identified as priorities. The results showed that three priority areas received the most votes, specifically community outreach and education, providing affordable health care and engaging in complementary care practice. Stakeholders also agreed it is critical to 'include youth in the conversation' when planning for cancer support and educational programmes for caregivers, friends and family members. Conclusion: Storytelling as a patient engagement approach can build trust in the patient‐research partnership, ensure that patients are meaningfully engaged throughout the process and capture the diversity of patient experiences and perspectives.